Chronic nonbacterial osteomyelitis in children: a retrospective multicenter study - Kaiser, Daniela (Pediatr Rheumatol Online J, 2015)
BACKGROUND: To determine the clinical presentation, current treatment and outcome of children with nonbacterial inflammatory bone disease. METHODS: Retrospective multicenter study of patients entered into the Swiss Pediatric Rheumatology Working Group registry with a diagnosis of chronic nonbacterial osteomyelitis (CNO) and synovitis acne pustulosis hyperostosis osteitis (SAPHO) syndrome. The charts were reviewed for informations about disease presentation, treatment, course and outcome. RESULTS: Forty-one children (31 girls and 10 boys) from 6 pediatric hospitals in Switzerland diagnosed between 1995 and 2010 were included in the study. The diagnosis was multifocal CNO (n = 33), unifocal CNO (n = 4) and SAPHO syndrome (n = 4). Mean age at onset of CNO was 9.5 years (range 1.4–15.6) and mean follow-up time was 52 months (range 6–156 months). Most patients (n = 27) had a chronic persistent disease course (>6 months), 8 patients had a course with one or more relapses and 6 patients had only one episode of CNO. Forty nine percent had received at least one course of antibiotics. In 57 % treatment with nonsteroidal anti-inflammatory drugs (NSAID) was sufficient to control the disease. Twelve out of 16 children with NSAID failure subsequently received corticosteroids, methotrexate, TNF α inhibitors, bisphosphonates or a combination of these drugs. CONCLUSIONS: In a multicenter cohort of 41 children 22 % started with unifocal lesion with a significant diagnostic delay. A higher proportion presented with chronic persistent disease than with a recurrent form. An osteomyelitis in the pelvic region is significantly associated with other features of juvenile spondylarthritis.